A rare case of intracranial malignant triton tumor arising in the middle cranial fossa: a case report and review of the literature - Bruzzone, Eros; Melloni, Ilaria; Barra, Salvina; Fraternali Orcioni, Giulio; Cocito, Leonardo (Folia Neuropathologica, 2018)
We describe a rare case of intracranial malignant triton tumor (MTT) arising in the middle cranial fossa in a 74-year-old female patient who had previously been exposed to radiation in the Chernobyl disaster. The patient underwent a surgical subtotal removal of the mass and radiation therapy, but the progression-free survival was only 2.5 months and death occurred four months after the onset of symptoms. MTTs are rare aggressive tumors arising from the nerve sheath showing rhabdomyosarcomatous differentiation and associated with a poor prognosis. The intracranial location is very rare, and only 10 cases, including the present report, have been described so far. Among intracranial MTTs, the cerebellopontine angle is the most common location. Neurofibromatosis type 1 (NF-1) and radiation exposure are risk factors as for MTTs located in other sites. The gold standard therapy is surgical excision followed by radiation therapy, but the prognosis is usually very poor.